Thermochromic smart windows with highly regulated radiative cooling and solar transmission - Wang, Shancheng (2022)
Radiative cooling (RC) is a technique that spontaneously radiates long-wave infrared (LWIR) to the cold outer space, which provides cooling power to buildings, however only preferred in hot seasons. RC has been widely researched on walls and roofs but rarely on windows while windows are the least energy-efficient part of buildings. Moreover, in the current smart window design, consideration of tunable RC is missing. For the first time, we proposed an ideal smart window with a switchable front side LWIR emissivity (εFront) and solar modulation ability (ΔTsol). Such window needs not only to have high luminous transmission (Tlum) and ΔTsol, the two major conventional performance indexes but also possess a switchable εFront to cater for the variable seasonal thermal performance requirements and energy-saving demands. We further fabricated a tunable emissivity thermochromic (TET) smart window with large ΔTsol (51%) and Tlum (72%) and switchable εFront (0.95–0.1) to prove the efficacy of the proposed ideal window. Compared with current smart window technology solely regulating solar transmission and other RC materials with fixed emissivity, the TET smart window panel gives a wide tunability in the selective solar spectrum for dynamic climate conditions in energy-saving buildings, achieving largely enhanced energy saving performance globally.